2012
DOI: 10.1002/anie.201205072
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Gold Fluorides and Noble Gas Complexes by Matrix‐Isolation Spectroscopy and Quantum‐Chemical Calculations

Abstract: Noble with a difference: Matrix-isolation experiments and quantum-chemical calculations have led to the characterization of two new compounds, namely first open-shell binary gold fluoride, AuF(2), and a NeAuF complex. Moreover, ArAuF, AuF(3), Au(2)F(6), and monomeric AuF(5) have been produced and identified under cryogenic conditions in neon and argon matrices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
36
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 48 publications
5
36
0
2
Order By: Relevance
“…In this context it is interesting to note that quantum‐chemical calculations predict the stretching mode of Au I F at this position in the spectrum. However, it has been shown that even at 4 K in a noble gas matrix Au I F only exists when coordinating a noble gas atom, due to its high Lewis acidity . Other gold fluorides that might be intermediates of the decomposition of Au III F 3 to Au 0 are [Au III F 2 ] + , [Au I F 2 ] − , [Au 2 F 2 ], in addition to adducts of these compounds with AuF 3 .…”
Section: Resultsmentioning
confidence: 99%
“…In this context it is interesting to note that quantum‐chemical calculations predict the stretching mode of Au I F at this position in the spectrum. However, it has been shown that even at 4 K in a noble gas matrix Au I F only exists when coordinating a noble gas atom, due to its high Lewis acidity . Other gold fluorides that might be intermediates of the decomposition of Au III F 3 to Au 0 are [Au III F 2 ] + , [Au I F 2 ] − , [Au 2 F 2 ], in addition to adducts of these compounds with AuF 3 .…”
Section: Resultsmentioning
confidence: 99%
“…[2][3][4][5] Interestingly, for these coinage metal halide complexes, the binding energy of helium was greater than neon in the respective molecules, although argon was more strongly bound than both neon and helium; the NeAuF complex has now been identified experimentally. 6,7 The binding energy of a helium atom was greatest in HeCuF, at 2270 cm −1 , and a small amount of covalency was deduced. 2,4 In part, the fluorine atom acts to pull electron density towards itself, thus facilitating partial donation of 1s electron density into the virtual Cu orbitals from the incoming He atom, leading to the designation of these as a new type of weak interaction.…”
Section: Introductionmentioning
confidence: 99%
“…[24] Molecular AuF 3 is unknown and even evaporation in the gas phase leads to the formation of dimers and not mononuclear species. [25] Thef ree enthalpies of the reactions of the so far elusive complex [AuF 3 (NHC)] and literature known [AuF 3 (NCCH 3 )] and [AuF 3 (py)] to yield AuF 3 and the respective ligands were calculated and the results are summarized in Figure 1. TheN HC we chose was 1,3bis(2,4,6-trimethylphenyl)-4,5-dihydroimidazol-2-ylidene (SIMes) because it has as aturated backbone in the imidazolidine that is not easily fluorinated.…”
mentioning
confidence: 99%
“…Under these conditions both complex 1 and SIMes show higher solubility than the aurate;t hus,asecond substitution is favored as long as free SIMes is available. [25,29] Compounds containing the Au I Fmoiety are known to be rather instable and were isolated only as complexes with strongly s-donating ligands like N-heterocyclic carbenes [16] or the Xantphos ligand [23] but are also unstable in the form [FAu I X] À (X = Cl, Br,I ). Thecomplex is most likely present as the Cl À salt after Cl/F exchange, because the highly nucleophilic fluoride reacts with the solvent dichloromethane at room temperature within af ew hours (SI Figures S-2 and S-3).…”
mentioning
confidence: 99%